2023
DOI: 10.15789/2220-7619-pvo-2043
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of specific cytokines for lethal COVID-19 outcome

Abstract: In our study, we aimed to evaluate the significance of specific cytokines in blood plasma as predictive markers of COVID-associated mortality. Materials and methods. In plasma samples of 29 patients with PCR-confirmed COVID-19 we measured the concentrations of 47 molecules. These molecules included: interleukins and selected pro-inflammatory cytokines (IL-1, IL-1, IL-2, IL-3, IL-4, IL-5, IL-6, IL-7, IL-9, IL-12 (p40), IL-12 (p70), IL 13, IL-15, IL-17A/CTLA8, IL-17-E/IL-25, IL-17F, IL-18, IL-22, IL-27, IFN2, IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our research showed that there was a significant increase in concentrations among both COVID-19 survivors and non-survivors when compared to healthy individuals. However, there was no statistical significance found when comparing the survivors and non-survivors [46]. And while it is possible that IL-27 may have predictive value, our analysis showed no sufficient sensitivity or specificity to support this claim.…”
Section: Interleukin 27 In Covid-19contrasting
confidence: 71%
“…Our research showed that there was a significant increase in concentrations among both COVID-19 survivors and non-survivors when compared to healthy individuals. However, there was no statistical significance found when comparing the survivors and non-survivors [46]. And while it is possible that IL-27 may have predictive value, our analysis showed no sufficient sensitivity or specificity to support this claim.…”
Section: Interleukin 27 In Covid-19contrasting
confidence: 71%
“…As the pandemic progressed, newer points of interest emerged: for instance, we investigated the value of cytokine profiling in acute infection and persisting patterns in convalescent patients [21]. We also explored predictors of disease severity among cytokines/chemokines [22], and we suggested a model for prognosis of the disease outcome. However, as the virus changed, we have realized that the immunological landscape went through certain changes as well.…”
Section: Changes In Mdc/ccl22 Concentrations In Covid-19 In Vitro And...mentioning
confidence: 99%
“…Specifically, researchers highlighted a significant shortage of DCs in COVID-19 patients, both in acute and post-recovery periods. Moreover, other studies have highlighted the relationship between disease severity [2] and dendritic cell properties [5], both quantitative and qualitative. This, however, for some reason does not affect other cytokines and chemokines, produced by DCs (IL-1α, IL-1β, IL-6, IL-7, IL-12 (p35 and p40), IL-15, IL-18, TNFα, TGF-β, macrophage CSF, and granulocytemacrophage CSF, but not IL-2, IL-3, IL-4, IL-5, IL-9, and IFNγ transcripts).…”
Section: Resultsmentioning
confidence: 99%